1988
DOI: 10.1007/bf02366099
|View full text |Cite
|
Sign up to set email alerts
|

Regional persistence of locally unstable predator/prey populations

Abstract: Nachman. G., 1988. Regional persistence of locally unstable predator/prey populations. Exp. Appl.Acarol., 5: 293-318.Phb¢oseiid mites are efficient predators capable of completely destroying colonies of spider mites. Thus, coexistence of phytoseiids and their tetranychid prey at a local scale (typically an individual plant) is not likely for more than a single predator/prey cycle. However, the species may coexist at a regional scale, i.e. in a complex environment consisting of many plants, provided local colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 71 publications
0
16
0
2
Order By: Relevance
“…The larger and the more spatially heterogeneous a system is, the less likely it is that local dynamics will synchronise (Taylor 1988(Taylor , 1990Fahrig and Paloheimo 1988;Hanski 1991). Detailed laboratory experiments on predator/prey systems have confirmed these theories (Huffaker 1958;Nachman 1988Nachman , 1991Lawler 1996a, 1996b).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The larger and the more spatially heterogeneous a system is, the less likely it is that local dynamics will synchronise (Taylor 1988(Taylor , 1990Fahrig and Paloheimo 1988;Hanski 1991). Detailed laboratory experiments on predator/prey systems have confirmed these theories (Huffaker 1958;Nachman 1988Nachman , 1991Lawler 1996a, 1996b).…”
Section: Discussionmentioning
confidence: 73%
“…dieffenbachii system is comparable to predator/prey complexes where predators cause local extinctions of their prey (Huffaker 1958 ;Huffaker et al 1963 ;Nachman 1988Nachman , 1991Lawler 1996a, 1996b) and in which some predators do not disperse until their local prey population is extinct. McEvoy et al (1995) demonstrated that also some spatially structured biocontrol systems do not establish a stable pestenemy equilibrium at the local scale, but are locally unstable on a "search-destroy" basis.…”
Section: Discussionmentioning
confidence: 99%
“…Movement of mites in a colony or patch occurs frequently, is mostly by ambulatory means, and has a low risk for mortality (Strong et al, 1999). Larger movement of mites from one isolated plant to another (interpatch) occurs less often and has more risk for mortality than intrapatch movement (Nachman, 1988). Interpatch movement is affected by many factors including temperature and humidity, wind and spatial structure of the patch, and loss of food supply (Strong et al, 1997(Strong et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…This work, we believe, opened the door to a major body of research on what has become known as metapopulation dynamics, which has dominated the past decade. The various experimental and theoretical developments that led up to, and consisted of the early stages of this new era of ecological research are eloquently discussed in Nachman's (1988 ) contribution to the proceedings of the first symposium on population dynamics of plant mites (a meeting that also led to the foundation of the European Association of Acarologists).…”
mentioning
confidence: 99%